Novel imprint of a dark photon from the 3-3-1-1 model - Doan, Minh Luong; Phung, Dong Van; Nguyen, Huy Thao (Communications in Physics, 2025)
We investigate a dark photon that arises from the UV model based upon \(SU(3)_CSU(3)_LU(1)_X U(1)_G\) (3-3-1-1) gauge symmetry, where the last three factors enlarge the electroweak symmetry encompassing electric charge \(Q=T_3 - 1/ 3T_8 +X\) and dark charge \(D = -2/3 T_8 +G\). It is well-established that this model addresses the questions of family number, neutrino mass, and dark matter. It is shown in this work that if the 3-3-1-1 breaking scale is much bigger than the dark charge breaking scale, the relevant dark gauge boson \(Z’\) is uniquely imprinted at TeV, avoiding dangerous FCNC processes, obeying precision electroweak measurements, as well as contributing to collider phenomena, even if no kinetic mixing is presented. The dark matter observables are perhaps governed by the dark charge breaking Higgs field instead of the dark photon.